Antivirulent Properties of Underexplored Cinnamomum tamala Essential Oil and Its Synergistic Effects with DNase against Pseudomonas aeruginosa Biofilms – An In Vitro Study - Farisa Banu, Sanaulla; Rubini, Durairajan; Rakshitaa, Sairam; Chandrasekar, Kamaraj; Murugan, Ramar; Wilson, Aruni; Gowrishankar, Shanmugaraj; Pandian, Shunmugiah Karutha; Nithyanand, Paramasivam (Frontiers in Microbiology, 2017)
Pseudomonas aeruginosa is a nosocomial pathogen colonizing patients with chronic infectious diseases and has gained resistance to all the known broad spectrum antibiotics available today. The present study showcases the antibiofilm potential of an essential oil (EO) from an underexplored Cinnamomum species namely, C. tamala, against P. aeruginosa biofilms. Furthermore, the synergistic effects of the EO along with a commercially available DNase (DNaseI) and a DNase (MBD) isolated from a marine bacterium were explored for its antibiofilm activity. The results showed that the synergized action has maximum efficacy in inhibiting young and preformed biofilms. The synergized effect of EO and DNaseI showed 70% inhibition against matured biofilms of P. aeruginosa. The EO from C. tamala also showed quorum sensing inhibitory potential as it could inhibit the swarming motility behavior of P. aeruginosa. The synergistic action of EO and DNases offers a novel alternate therapeutic strategy for combating P. aeruginosa biofilm associated infections.